Hubungan Kecemasan Sosial dengan Adiksi Media Sosial Instagram pada Emerging Adulthood - Wildatun Nisa'u Sholihah Darmawan; Muhammad Ilmi Hatta (UNISBA Press, 2022)
Abstract. Most people use the internet, one of which is accessing social media which functions as a way to avoid anxiety and as a substitute for face-to-face relationships that they do not get in everyday life because they are afraid to make direct contact with other people and prefer only online communication. However, excessive use of social media can lead to addiction. This study aims to see how closely the relationship between social anxiety and social media addiction to Instagram in emerging adulthood is in Bandung. The hypothesis in this study is that there is a positive relationship between social anxiety and social media addiction to Instagram in emerging adulthood in Bandung. The subjects of this study were 200 emerging adulthood students who were categorized as addicted to social media Instagram. This study uses the Social Anxiety Scale for Adolescent (SAS-A) from Greca & Lopez (1998) and the Social Media Disorder Scale (SMD Scale) from Eijnden, Lemmens, & Valkenburg, (2016). The analytical technique used is Spearman rank correlation test. The data obtained indicate that there is a strong positive relationship between social anxiety and social media addiction to Instagram in emerging adulthood in Bandung with a correlation value of 0.615 with a significance value of p = 0.000 <0.05. This means that the higher the level of social anxiety experienced by emerging adulthood in the city of Bandung, the higher the tendency for emerging adulthood to experience addiction to social media Instagram in Bandung. Abstrak. Kebanyakan orang menggunakan internet salah satunya mengakses media sosial berfungsi sebagai cara untuk menghindari kecemasan dan sebagai pengganti hubungan tatap muka yang tidak diperolehnya dalam kehidupan sehari-hari karena takut untuk melakukan kontak langsung dengan orang lain dan lebih memilih hanya komunikasi online. Namun penggunaan media sosial yang berlebihan dapat menyebabkan adiksi. Penelitian ini bertujuan untuk melihat seberapa erat hubungan antara kecemasan sosial dengan adiksi media sosial Instagram pada emerging adulthood di kota Bandung. Hipotesis pada penelitian ini adalah terdapat hubungan positif antara kecemasan sosial dan adiksi media sosial Instagram pada emerging adulthood di kota Bandung. Subjek penelitian ini adalah 200 mahasiswa berusia emerging adulthood yang terkategori adiksi media sosial Instagram. Penelitian ini menggunakan alat ukur Sosial Anxiety Scale for Adolescent (SAS-A) dari Greca & Lopez (1998) dan Social Media Disorder Scale (SMD Scale) dari Eijnden, Lemmens, & Valkenburg, (2016). Teknik analisis yang digunakan adalah uji korelasi rank spearman. Data yang diperoleh menunjukkan terdapat hubungan positif yang kuat antara kecemasan sosial dengan adiksi media sosial Instagram pada emerging adulthood di kota Bandung dengan nilai korelasi 0.615 nilai signifikansi p = 0.000 < 0,05. Artinya, semakin tinggi tingkat kecemasan sosial yang dialami emerging adulthood di kota Bandung maka semakin tinggi kecenderungan emetging adulthood mengalami adiksi media sosial Instagram di kota Bandung.